2020
DOI: 10.1111/1467-8551.12434
|View full text |Cite
|
Sign up to set email alerts
|

Evidence‐Based Management Competency Model for Managers in Hospital Settings

Abstract: Evidence-based management (EBMgt), which refers to using the best-quality evidence from different sources in decision-making, is becoming an imperative for managers in both profit and non-profit sectors. Yet, the competencies underlying EBMgt have not yet received much attention. Therefore, the aim of this study is to identify the foundational and functional competencies of evidence-driven managers working in hospital settings and develop an empirically based competency model for evidence-driven managers. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The present findings showed that in the fourth main step, “evidence acquisition and integration”, the most important sub-step was “finding the sources for seeking the evidence” [ 39 – 41 , 60 , 62 , 63 ]. Concerning the sources for the use of evidence in decision-making in HSM, studies have cited numerous sources, most notably scientific and specialized evidence such as research, articles, academic reports, published texts, books, and clinical guidelines [ 39 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…The present findings showed that in the fourth main step, “evidence acquisition and integration”, the most important sub-step was “finding the sources for seeking the evidence” [ 39 – 41 , 60 , 62 , 63 ]. Concerning the sources for the use of evidence in decision-making in HSM, studies have cited numerous sources, most notably scientific and specialized evidence such as research, articles, academic reports, published texts, books, and clinical guidelines [ 39 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 93%
“…Considering the third step and based on the knowledge extracted from the previous studies, the three sub-steps of “understanding context and Building Culture” [ 56 , 57 ], “gaining the support and commitment of leaders” [ 39 , 57 , 58 ], and “identifying the capabilities required by employees and their skills weaknesses” [ 58 60 ] were the most important sub-steps in this step of EBDM framework. In this regard, Dobrow (2004) has also stated that the two essential components of any EBDM are the evidence and context of its use [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one journal stated not very modestly, “change the world: teach evidence-based practice!” (Rynes et al , 2014). In a 2020 publication, Daouk-Oyry and colleagues say “EBMgt which refers to using the best‐quality evidence from different sources in decision‐making, is becoming an imperative for managers in both profit and non‐profit sectors” (Daouk-Oyry et al , 2020, p. 1). The website of the Academy of Management in May 2021 announces a new subpage called Academy of Management Insights, “bringing the best management research to business and society worldwide.…”
Section: Is Evidence-based Management a Fad?mentioning
confidence: 99%
“…Evidence‐based management (EBM) is defined as using the best available evidence for management decision‐making (Daouk‐Öyry, Sahakian, & Vijver, 2020). EBM has been associated with higher quality of care for acute myocardial infarction, congestive heart failure, and pneumonia (Tsai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%